Effect of Quorum Sensing Inducers and Inhibitors on Cytoplasmic Incompatibility Induced by Wolbachia (Rickettsiales: Anaplasmataceae) in American Serpentine Leafminer (Diptera: Agromyzidae): Potential Tool for the Incompatible Insect Technique. Issue 1 (23rd January 2022) - Hidayanti, Ardhiani Kurnia; Gazali, Achmad; Tagami, Yohsuke
Abstract: Agricultural crops around the world are attacked by approximately 3, 000–10, 000 species of pest insect. There is increasing interest in resolving this problem using environmentally friendly approaches. Wolbachia (Hertig), an insect endosymbiont, can modulate host reproduction and offspring sex through cytoplasmic incompatibility (CI). The incompatible insect technique (IIT) based on CI- Wolbachia is a promising biological control method. Previous studies have reported an association between CI and Wolbachia density, which may involve a quorum sensing (QS) mechanism. In this study, we investigated the effect of manipulating QS in Wolbachia using several chemicals including 3O-C12-HSL; C2HSL; spermidine (QS inducers), 4-phenylbutanoyl; and 4-NPO (QS inhibitors) on American serpentine leafminer ( Liriomyza trifolii [Burgess]), an agricultural pest. The results showed that inducing QS with 3O-C12-HSL decreased the proportion of hatched eggs and increased Wolbachia density, whereas QS inhibition with 4-phenylbutanoyl had the opposite effects. Thus, manipulating QS in Wolbachia can alter cell density and the proportion of hatched eggs in the host L. trifolii, thereby reducing the number of insect progeny. These findings provide evidence supporting the potential efficacy of the IIT based on CI- Wolbachia for the environmentally friendly control of insect pest populations.